Agrawal Flow Of A Hybrid Nanofluid Over A Shrinking Disk - Ishak, Anuar; Waini, Iskandar; Pop, Ioan (Elsevier Ltd, 2021)
This paper examines the influence of hybrid nanoparticles on Agrawal flow and heat transfer over a stretching/shrinking disk. The hybrid nanofluid consists of copper (Cu) and alumina (Al2O3) nanoparticles which are added into water to form Cu-Al2O3/water nanofluid. The similarity equations are obtained using a similarity transformation and the numerical results are obtained via bvp4c in MATLAB software. Findings discovered that dual solutions are possible for both shrinking (β < 0) and stretching (β > 0) cases. However, the solution is unique for β = 0 (static surface). Also, the skin friction coefficient is optimal on the static surface. Moreover, the rate of heat transfer is exaggerated with the increase of the hybrid nanoparticles. Further analysis proves that the first solution is stable and thus physically reliable, over time.